Supervisi Kepala Sekolah dalam Peningkatan Profesionalisme Guru di MIS Bidayatul Hidayah Rafa Kabupaten Deli Serdang - Ahmad Mukhlasin; Rabbirham; Raudatun Annisa; Siti Aisyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to evaluate the supervision of the principal in improving teacher professionalism at MIS Bidayatul Hidayah Rafa. This study uses a qualitative descriptive method, with data collection techniques through observation, interviews, and documentation. The results show that the principal's supervision plays a crucial role in enhancing teacher professionalism. The efforts made by the principal include coaching, training, and providing motivation. The challenges faced include limited time, lack of teacher awareness, and limited facilities and infrastructure. The solutions implemented are optimizing the supervision schedule, improving communication, and striving to provide adequate facilities and infrastructure. Overall, effective principal supervision, supported by comprehensive efforts, can improve teacher professionalism at MIS Bidayatul Hidayah Rafa.